High temperature reactions between Si3N4 bonded SiC materials and Cu, Cu2O and matte. Issue 1 (January 2018) - Jiang, Yang; Chen, Mao; Feng, Lijie; Chen, Junhong; Zhao, Baojun
Abstract: Si3 N4 bonded SiC (Si3 N4 -SiC) is a conventional refractory material and has broad applications. In the present study, Si3 N4 -SiC refractory materials were systematically investigated in the copper-making environment. Si3 N4 -SiC was reacted with Cu, Cu2 O, industrial matte, Cu2 S and FeS melts at 1200 °C in argon gas atmosphere, and all samples were directly quenched in water after the experiments. Phase changes and compositions of the phases were measured by electron probe X-ray microanalysis. The present investigations demonstrate that Cu and Cu2 S do not react with Si3 N4 -SiC at high temperatures and the wettability between this material and the melts is low. However, significant reactions occur between Si3 N4 -SiC and Cu2 O, industrial matte and FeS. The results imply that Si3 N4 -SiC material has limited oxidation-resistance and can only be used under reducing conditions.